THE DIABETIC PATIENT PHYSICAL ACTIVITY: A DESCRIPTION STUDY - Muhalla, Hafna Ilmy; Rahmadi Purwanto, Cucuk; Dunica Putri, Riza (Universitas Airlangga, 2024)
Introduction: Sedentary lifestyle in this modern era is one of the factors for the increasing incidence of diabetes mellitus. The high tendency of a person to be lazy to move and not do activities has various adverse effects on the human body, including an increased risk of death from various causes, including diabetes mellitus. However, there has been no research that more strongly explains the physical activity of patients with diabetes mellitus so far, especially in Lamongan Regency. The aim of this study is describing the physical activity of patients with diabetes mellitus in general hospitals in Lamongan Regency. Methods: This study is using a descriptive design by describing the physical activity of 50 diabetic patients at outpatient clinic. Data were collected using the Global Physical Activity Questionnaire (GPAQ) and analyzed by univariate analysis presented in the form of frequency tables. Results: The findings provide information that most 72% patients with diabetes mellitus have moderate physical activity. Conclusions: It is concluded that moderate physical activity in patients with diabetes mellitus makes patients still need to maintain stable blood sugar levels by doing regular and measured physical activity, and remain compliant with other diabetes mellitus management.